Effects of the normal sperm morphology rate on the clinical and neonatal outcomes of conventional IVF cycles. (20th March 2020) - Chen, Linjun; Li, Dong; Ni, Xiaobei; Zhu, Lihua; Zhang, Ningyuan; Fang, Junshun; Jiang, Weihua; Wang, Jie
Abstract: The present study assessed the influences of the normal sperm morphology rate on the clinical and neonatal outcomes of conventional in vitro fertilisation cycles. This retrospective study analysed 427 and 2, 728 cycles from the normal sperm morphology rate <4% and ≥4% group respectively. The clinical (total fertilisation failure, clinical pregnancy, implantation and abortion) and neonatal (sex, gestational age, preterm birth, birthweight, low birth weight, live births and birth defects of newborns) outcomes were compared. The rate of total fertilisation failure in the normal sperm morphology rate <4% group was significantly higher compared with that in the normal sperm morphology rate ≥4% group (2.8% versus 1.2%, p  = .012). Total fertilisation failure was completely resolved by early rescue intracytoplasmic sperm injection. The clinical pregnancy, implantation and abortion rates were not significantly different between the two groups. Additionally, the sex, preterm birth, low birth weight, live births and birth defect rates, gestational age and birthweight of newborns were not significantly different between the two groups. Thus, normal sperm morphology rate <4% significantly increased the total fertilisation failure rate but did not affect the clinical or neonatal outcomes.